Employing standardised methods to compare injury risk across seven youth team sports - Barden, C.; Quarrie, K. L.; McKay, C.; Stokes, K. A. (International Journal of Sports Medicine, 2021)
Injury surveillance systems seek to describe injury risk for a given sport, in order to inform preventative strategies. This often leads to comparisons between studies, although these inferences may be inappropriate, considering the range of methods adopted. This study aimed to describe the injury epidemiology of seven youth sports, enabling valid comparisons of injury risk. Consistent methods were employed across seven sports [male American football, basketball, soccer, rugby league, rugby union; female soccer and rugby union] at a high school in England. A 24-hour time-loss injury definition was adopted. Descriptive statistics and injury incidence (/1000 match-hours) are reported. In total, 322 injuries were sustained by 240 athletes (mean age=17.7±1.0) in 10 273 player-match hours. American football had a significantly greater injury incidence (86/1000 h; 95% CI 61-120) than all sports except female rugby union (54/1000 h; 95% CI 37-76). Concussion was the most common injury (incidence range 0.0-26.7/1000 h), while 59% of injuries occurred via player contact. This study employed standardized data collection methods, allowing valid and reliable comparisons of injury risk between youth sports. This is the first known study to provide epidemiological data for female rugby union, male basketball and American football in an English youth population, enabling the development of preventative strategies.